ELİLEPSİ HASTALARINDA HEMİSFERİK LATERALİZASYONUNUN OTONOMİK FONKSİYONLAR ÜZERİNE ETKİLERİ - TEKATAŞ, ASLAN (Fırat Üniveristesi, 2006)
[Abstract Not Available]
The effects of hemispheric lateralization on the autonomic functions in the epileptic patients
Keywords: Nöroloji